Pemodelan Anomali Magnetik Untuk Identifikasi Struktur Bawah Permukaan Bumi Di Nagari Cupak Kabupaten Solok - Ahmad Furqan; Dwi Pujiastuti; Dwi Puryanti; Ardian Putra (Universitas Andalas, 2024)
This research was conducted to determine the distribution of magnetic anomalies in the geothermal area of Nagari Cupak, Solok Regency using geomagnetic methods. Data was collected using a magnetometer at 144 observation points with a distance of 300 m between points. The magnetic anomaly value is obtained from the correction of daily variation’s total magnetic data and correction to the magnetic field value of the 13th generation IGRF (International Geomagnetic Reference Field) reference model. Furthermore, reduction to the poles and continuation upwards with a height of 200 m are carried out to remove noise and separate local and regional magnetic anomalies. After data processing, the total magnetic anomaly value in the area ranges from 1252.8 nT to 2969.4 nT which is categorized as low. The low anomaly value is thought to be caused by the demagnetization of rocks due to the influence of geothermal sources in the subsurface. Furthermore, 2D modeling is carried out by analyzing the magnetic anomaly data and making a cross-sectional incision of the model on the contour of the magnetic field anomaly that has been processed above. Based on the modeling results, the subsurface geothermal system of Nagari Cupak, Solok Regency, consists of a cover rock layer, reservoir layer, and hot rock layer which is suspected to be the heat source of the geothermal system of the study area.